Collaborative Awareness for Translation Groupware - Yong, Lim Tek (2009)
Translation is a process that allows people to learn and comprehend others' ideas or cultures in their own language. Such knowledge sharing will bring major advancement on society and the economy. A translation groupware, that allows two or more human translators to edit the output of machine translation at different times and different places, is developed in order to overcome the limitation of human translators and machine translation. However, translation groupware still not widely adopted by current human translators and the effectiveness is not known. An understanding of how multiple translators work and interact within a group is vital to develop a usable groupware. It is hypothesised that collaborative awareness can improve the translation groupware usability. Collaborative awareness components, such as interpersonal space and shared workspace, are identified as important characteristics to enhance the usability of translation groupware.